Deoxygenation of the Baltic Sea during the last millennium - Börgel, Florian; Neumann, Thomas; Rooze, Jurjen; Radtke, Hagen; Barghorn, Leonie; Meier, H. E. Markus (Frontiers in Marine Science, 2023)
Over the last 1,000 years, changing climate strongly influenced the ecosystem of coastal oceans such as the Baltic Sea. Sedimentary records revealed that changing temperatures could be linked to changing oxygen levels, spreading anoxic, oxygen-free areas in the Baltic Sea. However, the attribution of changing oxygen levels remains to be challenging. This work simulates a preindustrial period of 850 years, covering the Medieval Climate Anomaly (MCA) and the Little Ice Age using a coupled physical-biogeochemical model. We conduct a set of sensitivity studies that allow us to disentangle the contributions of different biogeochemical processes to increasing hypoxia during the last millennium. We find that the temperature-dependent mineralization rate is a key process contributing to hypoxia formation during the MCA. Faster mineralization enhances the vertical phosphorus flux leading to higher primary production. Our results question the hypothesis that increased cyanobacteria blooms are the reason for increased hypoxia in the Baltic Sea during the MCA. Moreover, the strong contribution of the mineralization rate suggests that the role of temperature-dependent mineralization in current projections should be revisited.